Museum Budaya dan Tantangannya: Kajian Multiperspektif di Papua - Dabamona, Samsudin Arifin; Idris, Muhammad Farid; Akbar, Mohammad Aldrin; Salim, Mursalam (Lembaga penelitian dan pengabdian kepada Masyarakat, 2022)
Museums, especially cultural museums have always been considered as gatekeepers of culture that put forward the main concepts of cultural preservation and conservation. Cultural visit to museums is effective stimulant in increasing cultural awareness, as well as strengthening the cultural identity of visitors. This paper explores the challenges of developing museums and Papuan culture from various perspectives. The discussion also highlights the transformation of museums into Papuan culture and the point of view of ideal conservation and preservation values based on the experiences and views of the group participants. Through qualitative research, the study formed three big themes: 1) Collection and space management; 2) Museum Image; and 3) human resources capacity building and moral responsibility. To improve services in the field of culture, the study suggested that museums in Papua need to think to strengthening museum management collection while providing visiting convenience and increasing support staff in the cultural field